Reconceptualizing the U.S. Military’s Transition Assistance Program: The Success in Transition Model - James Whitworth; Ben Smet; Brian Anderson (Journal of Veterans Studies, 2020)
This article describes and proposes the Success in Transition Model as a guiding framework for a reconceptualized Transition Assistance Program (TAP) to support U.S. military members as they leave the service. Key groups of veterans have ongoing difficulties adjusting to civilian settings after their time in the service. Even with recent changes, the current TAP has a narrow focus of primarily aiding members to prepare for finding post-military employment, education, and benefits. Little attention is given to other key areas of their functioning such as adjusting to their new work/educational/cultural settings, meeting family transition needs, financial management issues, procuring housing, dealing with trauma responses, or assuring that veterans truly obtain the benefits and support they need. This new model addresses key flaws with the current TAP and is grounded in human and military transition theories and research into optimal ways to foster improved outcomes for transitioning military members.